Redescription of Eutrombidium tehranicum (Acari: Trombidiformes: Microtrombidiidae), with two new synonyms and remarks on related taxa - Fardin Faizi; Hamidreza Hajiqanbar; Ali Asghar Talebi; Mohammad Mehrabadi; Alireza Saboori; Masoud Hakimitabar (Persian Journal of Acarology)
We redescribed and illustrated Eutrombidium tehranicum Karimi Iravanlou, Kamali & Talebi, 2002 based on the examination of type material, and new materials collected from three provinces (Kurdestan, Kermanshah, and West Azarbaijan) on new hosts of grasshoppers (Tettigoniidae and Acrididae). Eutrombidium elborzensis Karimi Iravanlou, Kamali & Talebi, 2002 and E. fathipouri Karimi Iravanlou, Kamali & Talebi, 2002 are considered junior synonyms of E. tehranicum. This study provides an updated and corrected description, illustrations, and host records for E. tehranicum, along with a discussion of its taxonomic status and distribution.